Academic library directors’ use of statistical data - Saarti, Jarmo; Juntunen, Arja; Laitinen, Markku; Taskinen, Aino (Qualitative and Quantitative Methods in Libraries; Vol 9 No 2 (2020): June 2020 Issue, 2020)
There has been an ongoing discussion about the input of the libraries to the output of the universities. The challenge here seems to be that a clear correlation is difficult to determine without in depth conducted research and analysis. The libraries on the other hand must prove their value to their parent organizations in order to manage the on-going survival game of the academic resource allocation and the competition with different actors within the academic information dissemination. We analyze in our paper how the statistical data is utilized in comparing the success of the universities, their output and in addition the resources and the use of their libraries. The comparison is done between five Finnish universities. Their selection is based on their similar size and academic structure. The main source of the data is interviews conducted with the library managers.